Path-dependence, lock-in, and student perceptions of nuclear energy in France: Implications from a pilot study. (July 2015) - Lee, Roh Pin; Gloaguen, Silke
Abstract: Past energy development decisions can influence and constrain future choices, leading to a lock-in to a certain energy development path. As a large socio-technical system, such lock-in effects in an energy system extend beyond the techno-institutional environments to its human dimension. This paper represents an exploratory attempt to bridge the gap between individual and group level analyses of the human side of energy systems. A mix-methods study investigated how French engineering students view nuclear energy and why nuclear energy is perceived the way it is. Sixty-seven students participated in a survey and forty-three of them additionally took part in focus groups. Survey findings showed that participants not only strongly associated nuclear energy with specific imageries; they also exhibited a positive perceptual bias toward nuclear energy. Through focus group discussions, we identified six factors contributing to the observed positive nuclear perception namely historical development, education system, political environment, economy, media coverage and societal influences. These factors constitute sources of lock-in and represent barriers to societal support of energy developments that has relevance beyond France and nuclear energy. Implications of study findings for future research and energy decision-makers engaged in the task of changing a nation's energy system are discussed.